DESAIN DAN VALIDASI MODEL BASIS DATA PEMELIHARAAN KOMPONEN ARSITEKTUR GEDUNG SEBAGAI PENDUKUNG FACILITY MAINTENANCE MANAGEMENT (FMM) - Santosa, Stefanus; Suroso, Suroso; Suwarto, Suwarto; Setiyono, Karnawan Joko; Suwarno, Anung (Politeknik Negeri Semarang, 2024)
The problems that arise in Facility Maintenance Management (FMM) in Indonesia, which involve aspects of management, learning, and mutual understanding in the Common Data Environment (CDE), can be overcome one way by developing a database. To compile a good database, a database design method is required that is based on existing theories and standards. This research was conducted to design a database model with the scope of the object of architectural component maintenance of buildings starting from the stages of identifying needs, designing, and testing to users. The results of the study show that the database model obtained has the category of